EROSION POTENTIAL ANALYSIS USING USLE (UNIVERSAL SOIL LOSS EQUATION) METHOD FOR DETERMINATION OF SOIL MOVEMENT HAZARD LEVEL AND MITIGATION AT AREA ABOVE TUNNEL 1 CISUMDAWU FREEWAY SUMEDANG, WEST JAVA - Baehaqi, Iqbal
Tunnel 1 of Cisumdawu toll road construction’s caused decreasing vegetation cover and increased land’s slope, consecuently the potential of erosion and landslide increased. The objectives of this study was to determine potential erosion rate, tolerable erosion rate, and mitigation with land conservation effort to maintain tunnel 1 can be utilized sustainably. The research location was located in area above tunnel 1 of cisumdawu toll road which have land cover, 2 sloping land inlet and outlet, and 1 middle land. Potential erosion rate are determined by USLE method (Universal Soil Loss Equation). Sampling for slope was done by purposive sampling, and simple random sampling for soil sampling. After factors of erosion rate were determined, the results showed the erosion rate (A) and Erosion Hazard Level (EHL) on inlet sloping land is 2,597.16 tons / ha / year (Very Heavy), outlet sloping land 2,899.58 tons / ha / year (Very Heavy), and middle land 1,067.43 (Very Heavy). The tolerable erosion rate on inlet sloping land is 21.73 tons / ha / year, 17.38 tons / ha / year on outlet sloping land, and 28.36 tons / ha / year on middle land. Mitigation through land conservation efforts on inlet and outlet sloping land are changing land conservation efforts (P) medium bench terrace (0.15) to good bench terrace (0.04), crop management efforts (C) from no vegetation (0, 95) to be partially covered grass with blanket and hydroseeding (0.01), thereby reducing the erosion rate to 14.5 tons / ha / year on inlet sloping land and 16.27 tons / ha / year on outlet sloping land, with EHL (very mild) and (mild). In the middle land, with changing the value of factor (C) from cultivation (0.4) to mixed dryland forest (0.01) can reduce the erosion rate to 26.68 tons / ha / year (mild).